Effective Reconstruction of Functional Urethra Promoted With ICG-001 Delivery Using Core-Shell Collagen/Poly(Llactide-co-caprolactone) [P(LLA-CL)] Nanoyarn-Based Scaffold: A Study in Dog Model - Zhang, Kaile; Fang, Xiaolan; Zhu, Jingjing; Yang, Ranxing; Wang, Ying; Zhao, Weixin; Mo, Xiumei; Fu, Qiang (Frontiers in Bioengineering and Biotechnology, 2020)
Hypospadias and urethral stricture are common urological diseases which seriously affect voiding function and life quality of the patients, yet current clinical treatments often result in unsatisfactory clinical outcome with frequent complications. In vitro experiments confirmed that ICG-001 (a well-established Wnt signaling inhibitor) could effectively suppress fibroblast proliferation and fibrotic protein expression. In this study, we applied a novel drug-delivering nanoyarn scaffold in urethroplasty in dog model, which continuously delivers ICG-001 during tissue reconstruction, and could effectively promote urethral recovery and resume fully functional urethra within 12 weeks. Such attempts are essential to the development of regenerative medicine for urological disorders and for broader clinical applications in human patients.